Factor XI deficiency diagnosed following use of adalimumab - Cetin, Guven (Medknow Publications & Media Pvt Ltd, 2014)
Adalimumab is a drug used in the treatment of refractory psoriasis. We present a case of a 55-year-old male patient who developed petechiae and purpura after the ninth dose of adalimumab therapy. The results of laboratory investigations revealed factor XI (F.XI) deficiency. It should be recognized that F XI deficiency may develop in patients using long-term adalimumab, leading to increased risk of bleeding.